2022
DOI: 10.1017/ice.2022.129
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections and antibiotic utilization varies by coronavirus disease 19 (COVID-19) severity in hospitalized cancer patients: Analysis from the first phase of the pandemic

Abstract: Objective: To characterize bacterial infections and antibiotic utilization in hospitalized cancer patients with coronavirus disease 2019 (COVID-19) Design: Retrospective cohort study Setting: Tertiary cancer center in New York City Patients: Hospitalized cancer patients >18 years with COVID-19 between March 1, 2020 and May 31, 2020 Methods: Patients were classified with mild (room air), moderate (nasal cannula oxygen), or severe (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Two hundred-three studies were excluded because they did not report data on antibiotic use in COVID-19 patients. Of the remaining 77 studies, 29 studies were included in this systematic review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two hundred-three studies were excluded because they did not report data on antibiotic use in COVID-19 patients. Of the remaining 77 studies, 29 studies were included in this systematic review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies included in the systematic review, 18 studies were on the prevalence of bacterial infection and antibiotics use in hospitalized COVID-19 patients [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; of these studies, 5 reported on patients admitted to the intensive care unit [ 20 , 21 , 22 , 23 , 24 ]. Four studies reported on the efficacy of early antibiotic use in hospitalized COVID-19 patients [ 25 , 26 , 27 , 28 ]; four studies were on the use of sepsis biomarkers to improve antibiotic use among COVID-19 patients [ 29 , 30 , 31 , 32 ]; three studies were on the efficacy of antimicrobial stewardship programs and predictive models among COVID-19 hospitalized patients [ 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Data on bacterial coinfections in patients who are immunosuppressed are sparse, but there may be scenarios, such as patients with febrile neutropenia, in which empiric antibiotic therapy at the time of COVID-19 or other respiratory viral diagnosis is justified. 78 It is important that HCP also consider the possibility of coinfection with viruses other than the pandemic strain. The use of nonpharmacologic interventions (eg, mask use, social distancing) significantly disrupted the transmission of non-SARS-CoV-2 respiratory viruses during the first surge of the COVID-19 pandemic such that influenza activity decreased in March 2020 and remained at historic lows.…”
Section: Discussionmentioning
confidence: 99%
“…Maki et al also reported that secondary bacterial infection in COVID-19cancer patients increased with the severity of COVID-19, and with severe infection, 81% of patients had secondary bacterial infections[11]. De Costa et al reported that 57.9% of these ICU COVID-19 patients had secondary bacterial ventilatory-associated pneumonia, and 49.5% had MDRO bacterial infections (multi-drug resistant organism.…”
mentioning
confidence: 97%